Sensory neuron-specific sodium channel SNS is abnormally expressed in the brains of mice with experimental allergic encephalomyelitis and humans with multiple sclerosis - Black, Joel A. (The National Academy of Sciences, 2000)
Clinical abnormalities in multiple sclerosis (MS) have classically been considered to be caused by demyelination and/or axonal degeneration; the possibility of molecular changes in neurons, such as the deployment of abnormal repertoires of ion channels that would alter neuronal electrogenic properties, has not been considered. Sensory Neuron-Specific sodium channel SNS displays a depolarized voltage dependence, slower activation and inactivation kinetics, and more rapid recovery from inactivation than classical “fast” sodium channels. SNS is selectively expressed in spinal sensory and trigeminal ganglion neurons within the peripheral nervous system and is not expressed within the normal brain. Here we show that sodium channel SNS mRNA and protein, which are not present within the cerebellum of control mice, are expressed within cerebellar Purkinje cells in a mouse model of MS, chronic relapsing experimental allergic encephalomyelitis. We also demonstrate SNS mRNA and protein expression within Purkinje cells from tissue obtained postmortem from patients with MS, but not in control subjects with no neurological disease. These results demonstrate a change in sodium channel expression in neurons within the brain in an animal model of MS and in humans with MS and suggest that abnormal patterns of neuronal ion channel expression may contribute to clinical abnormalities such as ataxia in these disorders.